BDNF and BMI effects on brain structures of bipolar offspring: results from the global mood and brain science initiative. (11th October 2017) - Mansur, R. B.; Brietzke, E.; McIntyre, R. S.; Cao, B.; Lee, Y.; Japiassú, L.; Chen, K.; Lu, R.; Lu, W.; Li, T.; Xu, G.; Lin, K.
Abstract : Objective: To compare brain‐derived neurotrophic factor (BDNF) levels between offspring of individuals with bipolar disorders (BD) and healthy controls (HCs) and investigate the effects of BDNF levels and body mass index (BMI) on brain structures. Method: Sixty‐seven bipolar offspring and 45 HCs were included (ages 8‐28). Structural images were acquired using 3.0 Tesla magnetic resonance imaging. Serum BDNF levels were measured using enzyme‐linked immunosorbent assay. Multivariate and univariate analyses of covariance were conducted. Results: Significantly higher BDNF levels were observed among bipolar offspring, relative to HCs ( P > 0.025). Offspring status moderated the association between BDNF and BMI (F1 =4.636, P = 0.034). After adjustment for relevant covariates, there was a trend for a significant interaction of group and BDNF on neuroimaging parameters (Wilks'λ F56, 94 =1.463, P = 0.052), with significant effects on cerebellar white matter and superior and middle frontal regions. Brain volume and BDNF were positively correlated among HCs and negatively correlated among bipolar offspring. Interactions between BDNF and BMI on brain volumes were non‐significant among HCs (Wilks'λ F28, 2 =2.229, P = 0.357), but significant among bipolar offspring (Wilks'λ F28, 12 =2.899, P = 0.028). Conclusion: Offspring status and BMI moderate the association between BDNF levels and brain structures among bipolar offspring, underscoring BDNF regulation and overweight/obesity as key moderators of BD pathogenesis.